Energy Subsidy and Economic Production: The Evidence from Malaysia and Indonesia - Husaini, Dzul Hadzwan; Hooi, Hooi Lean; Kueh, Jerome (Universiti Sains Malaysia, 2016)
Energy subsidy policy is one of the most favorable policies implemented by many oil producer countries in improving their economic development. However, the economic outcome is still debatable due to the implications on economic efficiency, fiscal policy and et cetera. As two main oil producer countries in ASEAN 5, both Malaysia and Indonesia had allocated 5% of energy subsidy (% of GDP) averagely throughout the period of 1990-2014. This paper is intended to study the impact of energy subsidy on economic production in Malaysia and Indonesia by employing a dynamic panel data analysis. Our finding suggests that the energy subsidy affects the growth output positively in the long run. We conclude that energy subsidy is significant to promote economic growth in both countries. The absence of energy subsidy will bring harm to the economic growth. However, if a reduction of energy subsidy is essential to improve efficiency and fiscal pressure, we suggest the policymaker to implement some offsetting policies to cushion the economy from any shocks.